Students’ Attitude towards Science after Taking Chemistry - Magallanes, Amel L. (JPAIR Institutional Research, 2016)
Regardless of one’s major or field of specialization, science or Chemistry specifically, plays an enormous role in life. Chemistry has become an indispensable feature in creating innovative tools in teaching the fact that Chemistry informs, many thoughts and behaviors, students have not valued science in general and Chemistry in particular. Thus, this study utilized the quantitative research with the use of a questionnaire to collect necessary data for the study and the Sloven formula to determine students’ attitudes and level of confidence after taking introductory Chemistry subjects taught in tertiary level science courses at Centro Escolar University, Makati Branch. The findings confirmed that the CEU Makati students have high-level of confidence after taking up Chemistry. Male or female, whether a graduate from private or public high school shows the same confidence level after taking Chemistry in performing exploring and applying what they have learned in their everyday activities and to other science subjects. Furthermore, there is a significant relationship between students who take up a science-related course as to their attitude level and level of confidence after taking up Chemistry. Teachers should encourage and motivate students to develop a high positive attitude towards Chemistry through skills and their ability.